Familial pulmonary thromboembolism with a prothrombin mutation and antithrombin resistance. Issue 6 (June 2018) - Yoshida, Ritsu; Seki, Shingo; Hasegawa, Jun; Koyama, Tatsuya; Yamazaki, Koji; Takagi, Akira; Kojima, Tetsuhito; Yoshimura, Michihiro
Abstract: We describe the case of a 45-year-old man with congenital thrombophilia induced by antithrombin resistance. He had recurrent venous thrombosis without traditional risk factors or abnormal coagulation function and had a family history of venous thrombosis which included his mother, brother, and nephew. We suspected the association of hereditary antithrombin resistance, which has been reported in some cases of familial venous thromboses due to prothrombin mutations. Although prothrombin abnormality typically shows a bleeding tendency, variations of arginine at position 596 in the gene encoding prothrombin have been reported to conversely cause thrombosis. Therefore, we tested and detected antithrombin resistance in the patient's plasma. We also performed genetic analysis for his second filial generation, and found a missense mutation (c.1787G>A), resulting in a substitution of arginine for glutamine at position 596 (p.Arg596Gln) in the gene encoding prothrombin (called prothrombin Belgrade). The Gln596 substitution caused the susceptibility to thrombosis. This variation is the same as one previously reported in Serbia and India, and it is the third report in Japan. <Learning objective: Venous thrombosis is caused by multiple factors. However, approximately 20% of the patients with venous thrombosis of unknown cause have no risk factors. The present case had no known risk factors, rather he has a family history of thrombosis. Therefore, we suspected an association with inherited thrombophilia. Although several gene mutations have been found in some families with inherited thrombophilia, many mutations remain to be detected.>